Исчезнувшие верования и позабытые герои (кожевенный инструментарий в ритуалах эпохи бронзы степной и лесостепной Евразии) - Подобед, В.А.; Усачук, А.Н.; Цимиданов, В.В. (Материалы по археологии Северного Причерноморья, 2011)
In the Bronze Age a tanning craft was one of the well-developed crafts according to archaeological finds. The study of tanning production on materials of the Bronze Age steppe and forest steppe cultures focused mainly on a technology. The ritual aspect of the tanning craft and the semantics of related tools hardly attracted researchers' attention. The paper is aimed at filling in this gap. Let's stipulate the criteria for the selection of sources. Sometimes in the literature there are funerary complexes regarded by scholars as burials of tanners. However, the authors tend to attribute these graves without any use-wear examinations or without any mention whether such examinations have been done. The same is true for some tools found at the settlements. In the author's view, this approach implies a risk to attribute some objects as tanner's tools whereas they are not. Therefore, we tried to select complexes for the analysis as strictly as possible. All the known finds were divided into a number of blocks depending on what kind of tool (tools) they included. To sum up the paper it can be stated that behind the unpretentious appearance of the Bronze Age tanner's tools there is a very rich mythology that is almost forgotten so far. The collection of materials on the subject will undoubtedly reveal new nuances connected with the ritual use of tanning equipment. At the same time, it will check the validity of our assumptions. Therefore, a good-quality publication of tanner's tools, which should include a detailed description of the contexts of finds, with good drawings and with use-wear and archaeo-zoological analyses, is very desirable.